Self-image and self-esteem (Journal of Parents and Teachers, 1996)
Self-esteem is the personal appraisal that influences behavior and emotional state. It is formed through social experiences and can be improved by eliminating negative thoughts. Collaboration between family and education is essential to develop healthy self-esteem.
Keywords: self-esteem; self-worth; behavior; family